Researching the far right: theory, method and practice - Ashe, Stephen D.; Busher, Joel; Macklin, Graham; Winter, Aaron (Routledge studies in fascism and the far right, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright page -- Contents -- List of illustrations -- List of contributors -- Introduction: Researching the far right -- PART I: Disciplinary overviews -- 1. Political science approaches to the far right -- 2. Historians and the contemporary far right: To bring (or not to bring) the past into the present? -- 3. Sociological survey of the far right -- 4. Right thinking: Criminologists on right-wing extremism -- 5. Getting inside 'the head' of the Far Right: Psychological responses to the socio-political context -- 6. Neo-nationalism and far right studies: Anthropological perspectives -- PART II: Quantitative approaches and online research -- 7. Estimating the far right vote with aggregate data -- 8. Methods for mapping far right violence -- 9. Challenges and opportunities of social media research: Using Twitter and Facebook to investigate far right discourses -- 10. Big data and the resurgence of the far right within the United States of America -- 11. Researching far-right hypermedia environments: A case-study of the German online platform einprozent.de -- PART III: Interviewing the far right -- 12. Methodology matters: Researching the far right -- 13. Interviewing members of the white power movement in the United States: Reflections on research strategies and challenges of right-wing extremists -- 14. Life-history interviews with rightwing extremists -- PART IV: Ethnographic studies of the far right -- 15. An observational study of the Norwegian far right: Some reflections -- 16. Overcoming racialisation in the field: Practising ethnography on the far right as a researcher of colour -- 17. Negotiating ethical dilemmas during an ethnographic study of anti-minority activism: A personal reflection on the adoption of a 'nondehumanization' principle.